Functional miscibility and thermomechanical properties enhancement of substituted phthalic acetylated modified chitin filler in biopolymer composite - N. G. Olaiya; O. S. Obaseki; Gaber A. M. Mersal; Mohamed M. Ibrahim; Mahmoud M. Hessien; Olaiya Funmilayo Grace; Asif Afzal; Taslima Khanam; Ahmad Rashedi (Royal Society Open Science, 2022)
The miscibility between hydrophobic and hydrophilic biopolymers has been of significant challenge. This study used a novel simplified chitin modification method to produce phthalic chitin using phthalic anhydride in a substitution reaction. The FT-IR functional group analysis was used to confirm the substitution reaction. The modified chitin was used as compatibilizer in polylactic acid (PLA)/starch biocomposite to enhance its properties. The biocomposite was prepared using melt extrusion and compression moulding technique. The biocomposite's morphological, thermomechanical and water absorption properties were characterized using scanning electron microscope, tensile test, dynamic mechanical analysis, thermogravimetry analysis, differential scanning calorimetry, thickness swelling and water absorption test. The FT-IR study shows a successful substitution reaction of the amine hydrogen ion present in the chitin as opposed to substituting the hydrogen ion in the hydroxide group. The tensile and impact properties of biocomposite incorporated with modified chitin showed better results compared with other samples. The SEM images showed uniform miscibility of the modified biocomposite. The dynamic mechanical analysis showed improved modulus value with the incorporation of modified chitin. The thermal properties showed improved thermal stability of the modified biocomposite. Furthermore, the percentage of water absorbed by biocomposite with modified chitin is reduced compared with the PLA/starch biocomposite. The produced biodegradable ternary blend can be used as a substitute for plastics in industrial applications.